1994
DOI: 10.1111/j.2042-7158.1994.tb03715.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vagus Nerve and its Non-cholinergic Mechanism in the Modulation of Ethanol-induced Gastric Mucosal Damage in Rats

Abstract: The role of the cholinergic pathway in the vagus nerve in modulating gastric lesion formation by ethanol was examined, using an ex-vivo stomach chamber preparation. Subdiaphragmatic vagotomy significantly increased the lesion areas but lowered acid secretion and gastric mucosal blood flow (GMBF). Atropine had no effect, whereas pirenzepine antagonized ethanol-induced mucosal damage. All three procedures showed similar potencies in depressing acid secretion, but only pirenzepine reversed the fall in the GMBF pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Oral administration of absolute ethanol in rats is noxious for the stomach, affecting the gastric mucosa topically by disrupting its barrier and provoking pronounced microvascular changes in few minutes after its application. Thus, rapid and strong vasoconstriction is accompanied by rapid and vigorous arteriolar dilation and this combination of microvascular events induces damage in mucosal capillaries [22, 23]. Currently, there is consensus that the former deleterious effects of ethanol on gastric mucosa are consequence of enhanced lipid peroxidation and decreased glutathione (GSH) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of absolute ethanol in rats is noxious for the stomach, affecting the gastric mucosa topically by disrupting its barrier and provoking pronounced microvascular changes in few minutes after its application. Thus, rapid and strong vasoconstriction is accompanied by rapid and vigorous arteriolar dilation and this combination of microvascular events induces damage in mucosal capillaries [22, 23]. Currently, there is consensus that the former deleterious effects of ethanol on gastric mucosa are consequence of enhanced lipid peroxidation and decreased glutathione (GSH) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rapid and strong vasoconstriction is accompanied by rapid and vigorous arteriolar dilation, and this combination of microvascular events induces damage in mucosal capillaries. [23] Pathophysiology of ulcer is due to an imbalance between aggressive factors (acid, pepsin, Helicobacter pylori , and non-steroidal anti-inflammatory agents) and local mucosal defensive factors (mucus bicarbonate, blood flow, and prostaglandins). [4] The lipid peroxidation mediated by reactive oxygen species is an important cause of destruction and damage to cell membranes, and it is involved in the pathogenesis of acute mucosal injury induced by ethanol, ischemia-reperfusion, and indomethacin.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigators have demonstrated that the high doses of IG ethanol induce gastric mucosal damage in rats e.g. [31][32][33][34][43][44][45] We undertook limited gross and microscopic examination of the gastric mucosa from several possums that received the 3 g kg )1 IG ethanol and noted some haemorrhage and mucosal oedema (data not presented). This prompted us to consider a possible role for gastric mucosal damage in the ethanol-induced fall in TSF.…”
Section: Gastric Mucosal Damagementioning
confidence: 99%